2014
DOI: 10.1118/1.4897244
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amorphous selenium detector thickness on dual‐energy digital breast imaging

Abstract: Increased dSe improves CE breast imaging performance by increasing QDE of detectors at higher energies, e.g., 49 kVp. Although there is additional blur in the oblique angled projections of a DBT scan, the overall 3D d' for DBT is not degraded because the dominant source blur at these angles results from the reconstruction filters of the employed FBP algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
(45 reference statements)
2
20
0
3
Order By: Relevance
“…We show that the MTF is degraded by oblique incidence. This result is consistent with previous works on both direct‐ and indirect‐converting detectors . The MTF degradation is most pronounced along the ray incidence direction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We show that the MTF is degraded by oblique incidence. This result is consistent with previous works on both direct‐ and indirect‐converting detectors . The MTF degradation is most pronounced along the ray incidence direction.…”
Section: Discussionsupporting
confidence: 92%
“…The MTF was calculated with a digital breast tomosynthesis (DBT) system using a tungsten edge . Previous works have also shown that increasing the thickness of selenium results in more substantial MTF degradation . This arises because the incident ray traverses a broader path length through the x‐ray converter, yielding more blurring.…”
Section: Introductionmentioning
confidence: 99%
“…As a future work, the developed 3D cascaded system analysis described above can be integrated with detectability index calculation by introducing various task functions (Gang et al 2011, Tward and Siewerdsen 2008, Hu and Zhao 2014, Siewerdsen and Jaffray 2000, Gang et al 2012, Richard et al 2005 to evaluate the detectability of objects of interest, such as small microcalcifications and low contrast masses.…”
Section: Page 21 Of 27mentioning
confidence: 99%
“…Previously, 3D cascaded system analysis models have been developed and validated for both cone-beam computed tomography (CT) and DBT (Tward and Siewerdsen 2008, Zhao and Zhao 2008b, Zhao et al 2009, Hu and Zhao 2014, Siewerdsen and Jaffray 2003, Gang et al 2011. We have already reported a 2D cascaded system analysis model for a 50 μm pixel pitch CMOS APS detector named DynAMITe (Zhao et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, technological advances on x-ray flatpanel detectors (FPD) enabling large-area digital imaging that have made it become a major of applications in diagnostic imaging (e.g., radiography, mammography) [1,2], interventional procedures (e.g., angiography, image-guided surgery) [3,4], and non-medical imaging (e.g., security screening, non-destructive testing) [5]. Digital detectors in the imaging system, include x-ray image intensifiers, photostimulable phosphors and scintillator-photodiode arrays responds to energy in x-ray photons.…”
Section: Introductionmentioning
confidence: 99%